1999
DOI: 10.1176/ajp.156.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 5-HT2 Receptors in Schizophrenia: A PET Study Using [18F]Setoperone in Neuroleptic-Naive Patients and Normal Subjects

Abstract: This study failed to find the decrease in 5-HT2 receptors reported in postmortem studies of schizophrenia. The study had the power to detect a decrease of 25% or more in 5-HT2 receptors, which was anticipated on the basis of the previous postmortem studies. Thus, a primary serotonergic abnormality in schizophrenia, if one exists, is either small or unlikely to be at the level of the 5-HT2 receptors. This finding does not rule out a therapeutic role for 5-HT2 antagonists in schizophrenia, but it does suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
4
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 49 publications
5
43
4
2
Order By: Relevance
“…neither with regions-of-interest (ROI) based nor with a voxel-based analyses (Trichard et al, 1998;Lewis et al, 1999;Okubo et al, 2000;Verhoeff et al, 2000). However, both tracers suffer from a relatively low affinity for 5-HT 2A receptors and, thus, they have an insufficient signal-to-noise ratio in subcortical areas (Erritzoe et al, 2008).…”
Section: Included Cases Ofmentioning
confidence: 99%
“…neither with regions-of-interest (ROI) based nor with a voxel-based analyses (Trichard et al, 1998;Lewis et al, 1999;Okubo et al, 2000;Verhoeff et al, 2000). However, both tracers suffer from a relatively low affinity for 5-HT 2A receptors and, thus, they have an insufficient signal-to-noise ratio in subcortical areas (Erritzoe et al, 2008).…”
Section: Included Cases Ofmentioning
confidence: 99%
“…Three positron emission tomography (PET) studies showed no difference in 5-HT 2A/C receptor density between schizophrenic patients and controls (Lewis et al, 1999;Okubo et al, 2000;Trichard et al, 1998). Only one study revealed a decreased 5-HT 2A binding potential in the frontal cortex of six neuroleptic-naive schizophrenic subjects when compared to healthy controls (Ngan et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…The relationship between genetic and epigenetic association is graphically represented in Figure 2. The idea of epigenetic dysregulation of HTR2A in SCZ is consistent with the decreased amounts of HTR2A mRNA (Burnet et al 1996) and serotonin receptor type 2 density (B max ) (Lewis et al 1999) in post-mortem brains of SCZ patients compared to controls.…”
Section: Epigenetic Interpretation Of Htr2a Studies With Sczmentioning
confidence: 64%
“…In this article, we further develop the epigenetic theory and re-analyze a number of experimental findings in psychiatric genetics that suggest a series of candidate genes and chromosomal loci that may become the targets for epigenetic studies. distributed throughout the central nervous system and that the hallucinogenic drug LSD demonstrates high affinity for serotonin receptors (reviewed in Lewis et al 1999). To our knowledge, association of HTR2A with SCZ was first detected in a Japanese sample when a higher frequency of C allele of the 102T/C polymorphism was documented (Inayama et al 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation